Sociolinguistic Perspective on Digital Communication: Understanding Gen Alpha Language Use in Tiktok - Putri, Bernadeta Kartika Buana Prima; Soraya, Najwa; Rosalinah, Yanti (Golden Ratio of Data in Summary, 2025)
This study explores the sociolinguistic characteristics of Generation Alpha's language use on TikTok, a platform blending creativity and social interaction. Examining code-switching, slang, and the influence of visual elements highlights how these features shape digital identities and cultural expression. The research uses qualitative methods like content analysis and user interviews to reveal how Gen Alpha adapts language to TikTok’s standards while challenging traditional linguistic norms. The findings demonstrate that digital communication significantly impacts the language of today’s youth, showcasing Generation Alpha’s sensitivity and inventiveness in coining new terms driven by rapid technological advancements. Social, cultural, and technical factors influence these communication patterns, with video and visual exchanges enhancing communication skills, shaping social identities, and fostering intergenerational connections. This research emphasizes the role of platform-specific language practices in shaping teenage culture and advancing sociolinguistics in social media contexts. It concludes that Generation Alpha employs a relaxed, creative, and trend-sensitive vocabulary, particularly on TikTok, reflecting contemporary digital communication trends. The study underscores the importance of understanding language dynamics in an ever-evolving digital landscape.